Thermal study of nickel(II) pyrazolyl complexes - Takahashi, P. M. [UNESP]; Netto, A. V G [UNESP]; Mauro, A. E.; Frem, Regina C. G. [UNESP] (Springer Nature, 2005)
The thermal behavior of the pyrazolyl complexes [NiCl2(HPz) 4] (1), [Ni(NCS)2(HPz)4] (2), [NiCl 2(HdmPz)4]·2H2O (3) and [Ni(NCS) 2(HdmPz)4]·2H2O (4) (HPz=pyrazole, HdmPz=3,5-dimethylpyrazole) has been studied by thermogravimetry (TG) and differential thermal analysis (DTA). The TG data indicated that the thermal stability of [NiX2(HL)4] (X=Cl, NCS) compounds varies depending on the pyrazolyl ligand in the following order HL=HPz>HdmPz. From the thermal decomposition of 3 and 4 it was possible to isolate the intermediate compounds [Ni(μ-Cl)2(HdmPz)2] (3a) and [Ni(μ-1,3-NCS) 2(HdmPz)2] (4a), respectively. The final products of the thermal decompositions of 1-4 were identified as NiO by X-ray powder diffraction. © 2005 Akadémiai Kiadó, Budapest.
Keywords: DTA; Nickel(II); Pseudohalides; Pyrazoles; TG; Differential thermal analysis; Organometallics; Pyrolysis; Thermodynamic stability; Thermogravimetric analysis; X ray powder diffraction; Nickel compounds